Clinical and epidemiological characteristics of severe acute respiratory infection due to respiratory syncytial virus in children under 5 years - Mezarina Esquivel, Hugo Antonio (2016)
Objective: To compare the clinical and epidemiological characteristics of severe acute respiratory infection in children under 5 years old with and without infection due to respiratory syncytial virus. Material and methods: Retrospective study in a sample of 65 cases and 65 controls in children under 5 years old with acute respiratory infection (SARI) treated at the Pediatric Emergency Hospital during 2014. The diagnosis of RSV test was performed using direct inmufluorescencia (IFD) in nasal and throat samples (D3 Ultra DFA Respiratory Virus 8 ™ Screening & ID Kit). The results were expressed in absolute and relative terms; the analysis was performed by measures of central tendency, chi-square, “t” Student and Mann Whitney tests. Results: Significant differences were found between cases and controls in the average age in the month of infection, the average respiratory rate, use of mechanical ventilation in antibiotic treatment and diagnosis of bronchiolitis at medical discharge. Conclusions: The results show that there are clinical and epidemiological differences between the cases and controls.